1988
DOI: 10.1007/bf02334408
|View full text |Cite
|
Sign up to set email alerts
|

Double blind controlled randomized study on azathioprine efficacy in multiple sclerosis. Preliminary results

Abstract: The preliminary results of a double blind controlled prospective randomized trial of Azathioprine for therapeutic efficacy in 38 patients with Multiple Sclerosis are reported. Progression of the disease is significantly reduced in Azathioprine-treated group in comparison to Placebo-treated patients, but this effect is reached only after 3 years of treatment (P less than 0.025) regardless of the clinical course and without affecting relapse rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…At 3 years there was a significant RRR for azathioprine over placebo of 42% (95% CI 7-64%). Change in EDSS was reported in four studies which was statistically significant at 2 years (À0.22; 95% CI À0.44 to 0.00) [119][120][121][122] but not 3 years (À0.25; 95% CI À0.52 to 0.02) [119,121,122]. In a single study of 14 RRMS patients, the mean number of Gad-enhancing lesions was reduced by 64% from 2.26 per scan during the 6 month baseline assessment to 0.84 lesions per scan during 6 months of active treatment [125].…”
Section: Azathioprinementioning
confidence: 94%
See 2 more Smart Citations
“…At 3 years there was a significant RRR for azathioprine over placebo of 42% (95% CI 7-64%). Change in EDSS was reported in four studies which was statistically significant at 2 years (À0.22; 95% CI À0.44 to 0.00) [119][120][121][122] but not 3 years (À0.25; 95% CI À0.52 to 0.02) [119,121,122]. In a single study of 14 RRMS patients, the mean number of Gad-enhancing lesions was reduced by 64% from 2.26 per scan during the 6 month baseline assessment to 0.84 lesions per scan during 6 months of active treatment [125].…”
Section: Azathioprinementioning
confidence: 94%
“…A Cochrane review of five double-blind placebo-controlled studies of azathioprine [119][120][121][122][123] found a significant reduction in relapses favouring azathioprine at 2 years with a relative risk reduction (RRR) of 23% (95% confidence interval [CI] 12-33%) [124]. Using an intention-to-treat analysis where drop-outs were assigned the worst outcome, azathioprine remained superior to placebo with significant reduction in relapses.…”
Section: Azathioprinementioning
confidence: 97%
See 1 more Smart Citation
“…Has been used empirically in the treatment of multiple sclerosis since the early 60s, mostly in Europe, pioneered in France by Aimard [7], in Lyon, and Sabouraud [8] in Rennes. The first DBRPC trial was that of Milanese et al [9] in which AZA treated patients did better. This was not confirmed by Ellison et al in 1989 [10].…”
Section: Azathioprinementioning
confidence: 99%
“…No less than 21 clinical trials of azathioprine efficacy in multiple sclerosis have been published since the initial report in 1969)18] However, only five were randomised double-blind placebo-controlled trials involving a mix of patients with exacerbating/remitting, exacerbating/progressive and chronic progressive disease) [19][20][21][22][23] These studies differed in patient characteristics, definitions of exacerbation and disease progression, and methods of assessment. However, a recent meta-analysis convincingly showed that all five studies are remarkably consistent in their conclusions) 24) Azathioprine monotherapy given orally at dosages of 2 to 3 mg/kg/day appears to reduce exacer-bation rates within the first year of initiating treatment, but offers only a modest degree of protection against accumulating disability.…”
Section: Clinical Studiesmentioning
confidence: 99%